A Chemical Research on Three Red Algae Gracilaria bursa-pastoris, Phyllophora crispa and Laurencia obtusa var. pyramidata - C. Guven, Kasim; Coban, Burak; Erdugan, Huseyin (Asian Journal of Chemistry, 2014)
In this paper, the exogenic and endogenic compounds in three red algae Gracilaria bursa-pastoris, Phyllophora crispa and Laurencia obtusa var. pyramidata were reported. Exogenic compounds detected are oil components and other pollutants such as, saturated and unsaturated aliphatic, cyclic and aromatic hydrocarbons, BHT, nonyl phenol and halogenated compounds as hexachloroethane and 4-chlorophenol. Endogenic compounds were fatty acids and its esters, eicosane, squalene, phytol. The algae can be used for monitoring of the sea pollution.